Fontdevila, P., A. Laguado Duca y H. Cao. 40 años de informática en el estado argentino. Buenos Aires, Eduntref, 2008, 169 pp. - Ferrando, Karina (2008)
Fil: Ferrando, Karina. Universidad de Buenos Aires; Argentina.